Challenges and Opportunities for Women's Success in Entering Green Economy-Based Businesses: A Systematic Literature Review - Eviatiwi Kusumaningtyas Sugiyanto; Kesi Widjajanti; Ratna Wijayanti; Shujahat Ali (Universitas Pasundan, 2024)
This study aims to analyze the challenges and opportunities for women entrepreneurs to enter green businesses successfully. Moreover, to synthesize and review research on the green entrepreneurship topic in terms of theory, theme, methodology, and research setting. This study used a systematic literature review method based on the SPAR-4-SLR. The analysis is bibliometric and content analysis with Publish or Perish software as a database and VOSviewer software. A total of 31 articles were reviewed. The study shows that opportunities and challenges in entering the green economy come from both internal and external environments. The study identified the dominance of quantitative approaches in previous research and found that the typical research setting is a developing country in Asia. This study can help practitioners and researchers to know the opportunities and challenges in running a green business, thus enabling them to formulate policies, strategies, and guidelines to promote the sustainable development agenda. The selection of the study topic is based on the gap phenomenon, namely the enormous potential of women entrepreneurs in the development of a sustainable economy. This study reveals the trend of green entrepreneur research, ranging from theories, methods, and research settings.